Index of the Project Gutenberg Works of Walter Richard Cassels - Cassels, Walter Richard, 1826-1907; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2019)
"Index of the Project Gutenberg Works of Walter Richard Cassels" by Cassels is a scholarly compilation likely created in the late 19th century. This book serves as an index for multiple works by the author, primarily focused on critical analyses related to religious themes. The type of publication can be categorized under academic or theological writing, centering on inquiries into divine revelation and related subjects. The main content of the book revolves around Walter Richard Cassels' work "Supernatural Religion," which examines the reality of divine revelation through a critical lens. It consists of several volumes that dissect various aspects of Christianity, including the nature of miracles, interpretations of the Synoptic Gospels, and analyses of early Christian writings. The investigation delves into how miraculous events are perceived in relation to natural order and human reason, while also exploring the authorship and messages of various historical religious texts. Cassels seeks to provide a thorough examination of historical and biblical evidence to evaluate the claims of supernatural occurrences. (This is an automatically generated summary.)
Release date is 2019-05-21
Produced by David Widger
Keywords: Indexes